2017
DOI: 10.2151/sola.13a-005
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Wave Variation from the Troposphere to the Lower Thermosphere during a Stratospheric Sudden Warming Event: A Case Study

Abstract: High resolution Whole Atmosphere Community Climate Model (WACCM) simulations are used to study how gravity waves vary during a stratospheric sudden warming (SSW) event from the source region to the lower thermosphere. The variation of zonal mean momentum flux of resolved gravity waves (with zonal wavelengths less than 1600 km) during SSW are qualitatively consistent with those obtained from parameterized studies, mainly caused by the change of filtering by the mean zonal wind. At high latitude in the winter he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…It is possible that the GW enhancement in the mesosphere is not only due to less filtering of tropospheric GW -the GW source could also be at higher altitudes. Liu (2017) argues that the rather rapid change in the winter jet system is expected to be a source of GW variability during SSW as GWs can be excited by imbalance of jet flow (O'Sullivan and Dunkerton, 1995;Zhang, 2004). Gerrard et al (2011) found evidence that upward-propagating gravity waves were generated in situ by a stratospheric temperature enhancement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that the GW enhancement in the mesosphere is not only due to less filtering of tropospheric GW -the GW source could also be at higher altitudes. Liu (2017) argues that the rather rapid change in the winter jet system is expected to be a source of GW variability during SSW as GWs can be excited by imbalance of jet flow (O'Sullivan and Dunkerton, 1995;Zhang, 2004). Gerrard et al (2011) found evidence that upward-propagating gravity waves were generated in situ by a stratospheric temperature enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…As SSW events are associated with dynamical changes in the stratosphere and mesosphere over several days, effects on gravity waves in the upper mesosphere and lower thermosphere can be expected and have also already been observed and/or modelled: Yigit and Medvedev (2012), for example, report that gravity wave (GW) activity increases by a factor of 3 in the course of the warming modelled by them. Liu (2017) point out that at high latitude in the winter hemisphere the momentum flux varies rapidly during the SSW. Afterwards, the magnitude of the mesospheric momentum flux decreases significantly.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Yigit and Medvedev (2012), for example, used a global circulation model in order to show that the activity of GW of lower atmospheric origin is enhanced by a factor of 3 in the course of the modelled warming. Based on WACCM, Liu (2017) point out that the magnitude of the mesospheric momentum flux decreases significantly after the SSW event, but it varies strongly during the event. His findings agree with the observations of GW momentum flux changes during a SSW published by Wright et al (2010), France et al (2012), Thurairajah et al (2014), andErn et al (2016), for example.…”
Section: Discussionmentioning
confidence: 99%
“…Yigit and Medvedev (2012), for example, used a global circulation model in order to show that the activity of GW of lower atmospheric origin is enhanced by a factor of 3 in the course of the modelled warming. Based on WACCM, Liu (2017) point out that the magnitude of the mesospheric momentum flux decreases significantly after the SSW event, but it varies strongly during the event. His findings agree with the observations of GW momentum flux changes during a SSW published by Wright et al (2010), France et al (2012), Thurairajah et al (2014), and Ern et al (2016, for example.…”
Section: Discussionmentioning
confidence: 99%